Analisis Keterkaitan Tulisan Mushaf Al-Qur’an Rasm Utsmani Dalam Perubahan Emosional (Studi Tematik Surah Al-Baqarah Ayat 286) - Mitra, Rohma; Wulandari, Putri; Ali, Yasyfin Halim; Anggraini, Yola; Nasution, Sahkholid (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Humans are the most perfect created creatures, humans have reason and passion which are essentially used to worship Allah Ta'ala. So experts reveal that humans have emotional intelligence as an indication of their ability to understand the emotions of themselves and others. Human thoughts regarding emotional intelligence have been explained in the Al-Quran, so that in the Al-Quran you can find various kinds of emotions that occur in humans. This research aims to determine the relationship between emotional changes experienced by humans in Surah al-Baqarah verse 286 with the writings of Rasm Usmani. Carried out using the library file method, by quoting from various research sources published in various indexed journals. The result that can be seen is that this surah reveals that Allah has arranged everything that exists in this world, all the problems that are given to humans, are actually not beyond the limits of human ability, every problem experienced has its own way of solving it.